2020
DOI: 10.1007/s10533-020-00649-8
|View full text |Cite
|
Sign up to set email alerts
|

Fate and stability of dissolved organic carbon in topsoils and subsoils under beech forests

Abstract: Dissolved organic carbon (DOC) from Oa horizons has been proposed to be an important contributor for subsoil organic carbon stocks. We investigated the fate of DOC by directly injecting a DOC solution from 13 C labelled litter into three soil depths at beech forest sites. Fate of injected DOC was quantified with deep drilling soil cores down to 2 m depth, 3 and 17 months after the injection. 27 ± 26% of the injected DOC was retained after 3 months and 17 ± 22% after 17 months. Retained DOC was to 70% found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 83 publications
0
4
0
2
Order By: Relevance
“…Thus, subsoil microorganisms have to adapt themselves to such energy and carbon limited conditions. One major source of growth resources for microorganisms is the transport of dissolved organic matter derived through preferential flow paths from the organic layer to top soil layers and, especially to subsoils in forest ecosystems (Kalks et al, 2020;Nazari et al, 2020). This major nutritional source for subsoil microorganisms may substantially decrease in its availability to subsoil microorganisms, due to the destruction of preferential flow paths by compaction.…”
Section: Soil Microbial Biomass Carbonmentioning
confidence: 99%
“…Thus, subsoil microorganisms have to adapt themselves to such energy and carbon limited conditions. One major source of growth resources for microorganisms is the transport of dissolved organic matter derived through preferential flow paths from the organic layer to top soil layers and, especially to subsoils in forest ecosystems (Kalks et al, 2020;Nazari et al, 2020). This major nutritional source for subsoil microorganisms may substantially decrease in its availability to subsoil microorganisms, due to the destruction of preferential flow paths by compaction.…”
Section: Soil Microbial Biomass Carbonmentioning
confidence: 99%
“…The laboratory batch experiments included two additional sites under beech, Ebergötzen (Dystric Cambisols) and Rüdershausen (Haplic Luvisols), as did the related DOC injection experiment from Kalks et al. (2020) in order to investigate the sorption behavior of soils which developed on different parent materials (more details are provided in the Supporting Information Methods). For the three study sites, we refer to a soil depth between 0 and 10 cm as topsoil, 10 and 50 cm as upper subsoil, and 50 and 150 cm as deeper subsoil based on recent publications describing these sites (Kalks et al., 2020; Leinemann et al., 2016; Liebmann et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In line with this, Liebmann et al (24) found, in the same experiment as that of the present study, that a substantial part of the newly formed mineral-associated OC was labile. Pronounced C retention in topsoil has been further explained by preferential sorption of newly introduced C to already present organo-mineral clusters in a DOC injection experiment (45). Nevertheless, soil mineralogy and related physico-chemical properties can control the extent and temporal pattern of microbial assimilation of formerly mineral-bound C, but this may vary substantially between different soil types (46)(47)(48).…”
Section: Litter-derived Carbon Utilisation Across Depth and Over Timementioning
confidence: 99%